الحسن والقبح عند الزّمخشريّ والنّسفيّ :دراسة مقارنة: Good and Evil According to al-Zamakhshari and al-Nasafi: A Comparative Study - Syed Abdul Rahman, Syed Mohammad Hilmi; Sa’ari, Che Zarrina; Che Nordin, Mohd Khairul Naim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Mu’tazilites believed that al-Husn and al-Qubh could be determined and evaluated intellectually without the need for shara‘. Despite of agreeing with such views of al-Husn and al-Qubh, al-Maturidiyyah still rejected the Muktazilah’s opinion on rewards and sins and asserted that both were determined by shara‘, rather than by rational study. There are those who believed that the rewards and sins of all acts depend on shara‘ and they also agreed that reason can judge it. Besides, there are those who claimed the rewards and sins of some acts are merely valued by reason. This research used analytical descriptive method based on inductive to study al-Zamakhshari and al-Nasafi’s views on al-Husn and al-Qubh and to make comparisons between the two views. The study concludes that al-Zamakhshari insisted that reason is able to know the law of Allah on something based on al-Husn and al-Qubh because it is inherent in its actions. Thus, al-Zamakhshari interpreted verses containing the meanings of al-Husn and al-Qubh in the interpretation of ‘aqli and majazi, while al-Nasafi argued that reason can understand the meaning of perfection and imperfection and al-Husn and al-Qubh without shara‘. On the one hand, there was no disputed between al-Zamakhshari and al-Nasafi on al-Hasan is a state of perfection and al-Qabih is a deficiency. Nonetheless, when it comes to the issue of rewards and punishments associated with such actions, both were disputed against each other.